Horticultural therapy impact on people with dementia - Adi Vitman-Schorr; Moran Chen; Ayelet Naveh; Tamar Hirshenzon Peiper; Orly Ganany Dagan (BMC Geriatrics)
Abstract Background Dementia is a progressive disease, and as the disease progresses, many families seek help through activities and therapies. In contrast to some other therapies, horticultural therapy (HT) is widely accepted by most people with dementia (PWD) because it invites them to the natural world. Objectives To explore whether HT emotional and communication measures (i.e. appropriate expression of emotions, ability to communicate with others) are higher than in other activities offered to PWD in adult day care centers (ADCC) and continuing care retirement community (CCRC), and whether there is a difference between the impact of HT on the number of “positive actions” (communication actions and actions that fit the guided activity) vs. the other activities. Research design and methods Fifty-one PWD attending ADCCs and living in one CCRC were recruited to a structured HT activity and other activities that took place in the ADCCs and CCRC. The activity took place over 10 weeks. The effects were assessed using Dementia Care Mapping (DCM) and questionnaires. Results Paired t-tests found that higher levels of mood and behavior were observed during HT activities compared to the other activities. Also, communication and function actions were higher in the HT activities as compared to the other activities. Discussion and implications This study adds to the growing evidence of the benefits of HT for PWD regardless of past experience in gardening/agriculture. HT seems to provide high therapeutic benefits and should be more prevalent in centers caring for PWD.